Fabrication of green ZnO nanoparticles using walnut leaf extract to develop an antibacterial film based on polyethylene–starch–ZnO NPs - Saemi Rouhina (De Gruyter, 2021)
Zinc oxide nanoparticles (ZnO NPs) were synthesized utilizing prepared walnut leaf extract by various amounts of its leaves (5–25 g) via a heater and stirrer adjusted at 60°C and reaction time ranging from 30 to 90 min. Fourier transform infrared spectroscopy and gas chromatography indicated the six main functional groups and 29 bioactive compounds in the provided walnut leaf extract. Antioxidant and antibacterial inhibitory activities of the fabricated ZnO NPs, in powder form, were modeled as a function of two synthesized parameters using response surface methodology, and the fabrication process was optimized. The results indicated that the ZnO NPs synthesized using walnut leaf extract, with 15.51 g of its dried powder and reaction time of 60 min, had maximum antioxidant activity and antibacterial effects against Escherichia coli. X-ray diffraction analysis and scanning electron microscopy image indicated that the synthesized ZnO NPs using optimal processing conditions had crystals in triangular nanoprisms to nearly spherical shape with the particle size ranging from 15 to 40 nm. Finally, prepared biodegradable film composed of thermoplastic starch (5% w/w), polyethylene (93% w/w), and ZnO NPs (2% w/w) indicated high bactericidal inhibitory activity against both Gram-positive (Staphylococcus aureus) and Gram-negative (E. coli) bacterial strains.